2017
DOI: 10.1016/s2542-5196(17)30141-9
|View full text |Cite|
|
Sign up to set email alerts
|

Restricting the use of antibiotics in food-producing animals and its associations with antibiotic resistance in food-producing animals and human beings: a systematic review and meta-analysis

Abstract: SummaryBackgroundAntibiotic use in human medicine, veterinary medicine, and agriculture has been linked to the rise of antibiotic resistance globally. We did a systematic review and meta-analysis to summarise the effect that interventions to reduce antibiotic use in food-producing animals have on the presence of antibiotic-resistant bacteria in animals and in humans.MethodsOn July 14, 2016, we searched electronic databases (Agricola, AGRIS, BIOSIS Previews, CAB Abstracts, MEDLINE, Embase, Global Index Medicus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
533
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 693 publications
(554 citation statements)
references
References 30 publications
5
533
0
16
Order By: Relevance
“…This work reinforced the established understanding that reducing antimicrobial use in agriculture is associated with reductions in antimicrobial resistance in food producing animals, as well as the idea that, at minimum, the benefit appears to extend to farmers and those in direct contact with food producing animals 9. The authors clearly acknowledge the limitations in these reviews, and although there are few studies showing a direct effect on human health of antimicrobial use in animals, the overall body of evidence provided enough evidence to support WHO’s recommendations.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…This work reinforced the established understanding that reducing antimicrobial use in agriculture is associated with reductions in antimicrobial resistance in food producing animals, as well as the idea that, at minimum, the benefit appears to extend to farmers and those in direct contact with food producing animals 9. The authors clearly acknowledge the limitations in these reviews, and although there are few studies showing a direct effect on human health of antimicrobial use in animals, the overall body of evidence provided enough evidence to support WHO’s recommendations.…”
supporting
confidence: 60%
“…The new guidelines were shaped by published reviews commissioned by the WHO Advisory Group on Integrated Surveillance of AMR 89. This work reinforced the established understanding that reducing antimicrobial use in agriculture is associated with reductions in antimicrobial resistance in food producing animals, as well as the idea that, at minimum, the benefit appears to extend to farmers and those in direct contact with food producing animals 9.…”
mentioning
confidence: 99%
“…1). Moreover, according to [30], the decrease of the antibiotic resistance in animal matrices has already be linked to the reduction of antibiotic use in livestock.…”
Section: Relevant Outcomesmentioning
confidence: 99%
“…Several management options can be proposed to reduce the antibiotic use and to treat the organic wastes before their release in the natural compartments [13,29]. Recently, a systematic review showed that the restriction of antibiotic use in livestock can be associated with a decrease of antibiotic resistance in the animals and in farmers in contact with them [30].…”
mentioning
confidence: 99%
“…In recent years, there have been increasing concerns that the widespread use of antibiotics in food animal agriculture could lead to the emergence, spread, and propagation of bacteria that are antibiotic resistant. If these bacteria spread to human populations through food products, direct contact with animals, or via the environment, the resulting infections could be more difficult to treat if antibiotics of the same class or different classes of antimicrobials are used in both animals and in human medicine, leading to increased burdens of morbidity and mortality, and increased costs for care . To help navigate the complex set of medications involved and to ensure that the most essential drugs are used judiciously in both human and veterinary medicine, public and animal health organizations have created competing lists of “critically important antimicrobials” (CIAs) that rank these compounds according to their importance in human and veterinary medicine, respectively…”
Section: Introductionmentioning
confidence: 99%